Incidence of Gynecological Cancer in Comparison to Breast after 2003 in Baghdad (Eurasian Medical Research Periodical, 2022)
A broad range of illnesses that can affect any region of the body are collectively referred to as cancer. Goal: To examine the incidence of gynecological cancer in Baghdad after 2003 in comparison to breast cancer. The findings indicated that breast cancer affects more in Iraqi women than men in terms of prevalence and incidence of lung cancer. Females were more likely than males to develop any sort of cancer.